Sexual and reproductive rights and the criminalization of abortion as a biopower strategy (Revista Direito em Debate, 2022)
Women's sexual and reproductive rights give rise to great social and legal debate, and there is no denying the need to broaden the discussion in order to advance in the search for gender equality. The present article intends to make an analysis on the subject, dealing with the constructions of gender and human rights, the reproductive freedom of women, as well as the biopolitics and the control exercised over the female body, with emphasis on the analysis of the criminalization of abortion as a strategy biopolitics of control of female bodies. In order to develop the research, the deductive method will be used, with production based on books, articles and legislation on the subject, that is, a qualitative research.
Keywords: Human rights. Sexual and Reproductive Rights; Reproductive freedom. Biopolitics.